2010
DOI: 10.1111/j.1471-4159.2010.07072.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CD44 as a cell surface marker for Müller glia precursor cells

Abstract: In the retina, both neurons and glia differentiate from a common progenitor population. CD44 cell surface antigen is a hyaluronic acid receptor expressed on mature Mü ller glial cells. We found that in the developing mouse retina, expression of CD44 was transiently observed at or around birth in a subpopulation of c-kit-positive retinal progenitor cells. During in vitro culture, purified CD44/c-kit-positive retinal progenitor cells exclusively differentiated into Mü ller glial cells and not into neurons, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 31 publications
0
42
0
1
Order By: Relevance
“…[13]. HA might be an interesting molecule for ocular delivery as well since it is a major constituent of the vitreous humour [20], is found throughout the retina [21] and many retinal cell types have been shown to express CD44-receptors on their surface [22,23]. vitro with minimal cytotoxicity, owing to the repetitive disulfide linkages in the main poly(amido amine) backbone [9,24].…”
Section: Figure 1: Schematic Illustration Of Different Intra-ocular Amentioning
confidence: 99%
“…[13]. HA might be an interesting molecule for ocular delivery as well since it is a major constituent of the vitreous humour [20], is found throughout the retina [21] and many retinal cell types have been shown to express CD44-receptors on their surface [22,23]. vitro with minimal cytotoxicity, owing to the repetitive disulfide linkages in the main poly(amido amine) backbone [9,24].…”
Section: Figure 1: Schematic Illustration Of Different Intra-ocular Amentioning
confidence: 99%
“…5A). In addition, we observed that cells positive for CD44, which has recently been associated with astrocyte precursors in the developing central nervous system (49)(50)(51), displayed morphological abnormalities in infected dNP20 cultures (data not shown). Considering our present data together with previous findings, we propose that prions may induce cytopathic changes in astrocyte lineage cells, which may not differentiate into fully mature astrocytes.…”
Section: Discussionmentioning
confidence: 83%
“…However, some studies have showed CD44 expression in astrocytes during development and adult; astrocyte precursor cells in developing chick [4,5], mice and rat [6,7,22], Müller glial cells in mice retina [9]. In some human disease, CD44 expression was reported in astrocyte-restricted precursor cells or reactive astrocytes [3,23].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the CNS, CD44 expression was also reported in the retina. In mature mice retina, CD44 expressed on Müller glial cells [9]. In developing retina of the mice, CD44 was not detected at E15, transiently expressed in cells at around P1 day which will differentiate into Müller glial cells, and after P15 day it was increased to adult level [9].…”
Section: Introductionmentioning
confidence: 93%